Physical Defense Planning Against Voltage Distortion Attacks in Active Distribution Grids - Kuroptev, Kirill; Hajikazemi, Sina; Steinke, Florian (IEEE access, 2025)
The growing number of distributed energy resources (DER) in distribution grids increases the occurrence rate and magnitude of voltage deviations. DER-inverters are able to counteract these deviations via voltage/VAr control. In addition, modern DER-inverters, as part of the Internet of Things, are potentially subject to cyber attacks, potentially targeting voltage distortions to destabilize distribution grid operations. This work proposes a novel trilevel defender-attacker-operator problem that enables system operators to physically defend against cyber-induced risks of voltage distortion attacks due to manipulated DER-inverters. The problem considers uncertainties of DERs' power injections and loads, bidirectional power flows, and simultaneous under- and overvoltages contributing to a holistic defense design. For the defense, the system operator places voltage support devices, such as capacitors or distribution grid static compensators, to protect the system and counteract the cyber-induced voltage distortions in the worst realization of DERs' power injections and loads. A column and constraint generating algorithm is proposed that efficiently solves the trilevel problem. Results for the IEEE 13 bus and IEEE 123 bus test grids implicate the proposed algorithm's high efficiency and effectiveness in finding optimal defense strategies against voltage distortion attacks.